Exploring barriers to parent-adolescent sexual-risk communication among adolescents in Port Harcourt Nigeria: Adolescents' and parents' perspective. - Chidinma Joycelyn Okpalaku; Chigozirim Ogubuike (PLOS Global Public Health)
Adolescent risky sexual behaviour is a public health problem with its deleterious outcomes. Parents are the most influential source of sexuality education to adolescent, yet adolescents' lack sexuality educations. The study explored barriers in parent-adolescent sexual-risk communication from both perspectives in Port-Harcourt LGA, Rivers State. A cross-sectional study design using explanatory sequential mixed methods approach was implemented. Three hundred and twenty nine in-school adolescents participated in the quantitative study and recruited using multi-stage sampling technique while 9 parents of adolescents and 16 adolescents participated in the qualitative study. A self-administered questionnaire was used to elicit information from the adolescents while an FGD and IDI guide was used to elicit information from in-school adolescents and parents respectively. The quantitative data was analysed using descriptive statistics and chi-square while the qualitative data was subjected to thematic analysis. The mean age of the adolescents was 16.0 ± 1.1 years and 55% were males. 21% of the parents had never discussed sex with their adolescents. The barriers identified from the adolescents' perspective were parental factors (parents being too busy, judgmental, low knowledge), individual factors (discomfort to initiate communication, lack of trust), religious and cultural factors. The barriers from the parents' perspective were shame to initiate communication, fear of outcome, feeling children are too young and lack of accurate information. The barriers to parent-adolescent communication featured interplay of parental, individual, cultural and religious factors. Parents should be trained to initiate timely and accurate sexuality education to the adolescent to curb adolescent risky sexual exploitations.